2014
DOI: 10.1111/pai.12186
|View full text |Cite
|
Sign up to set email alerts
|

Use of IgE and IgG4 epitope binding to predict the outcome of oral immunotherapy in cow's milk allergy

Abstract: Background Oral immunotherapy (OIT) with cow's milk (CM) has been reported to induce a number of specific antibody responses, but these remain to be fully characterized. Our objective was to explore whether IgE and IgG4 epitope binding profiles could predict the risk of side effects during cow's milk OIT. Methods The study population consisted of 32 children (6 – 17 years of age) with cow's milk allergy: 26 children who successfully completed OIT and 6 children who discontinued therapy due to adverse reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 27 publications
2
67
1
2
Order By: Relevance
“…34 AA16e35 and AA34e53 in k-casein were also Time-related differences in the binding of IgE and IgG4 to epitopes of b-lactoglobulin, a-lactalbumin, and caseins between patients with early recovery or persistent cow's milk allergy have been investigated. 101,102 Furthermore, IgE and IgG4 epitope binding was also analyzed to predict the outcome of oral immunotherapy in cow's milk allergy using peptide arrays. 103 The results of this study showed that monitoring the binding of IgE and IgG4 to epitope peptides of caseins has predictive value for the development of tolerance to cow's milk or the outcome of oral immunotherapy.…”
Section: B-casein (Bos D 11)mentioning
confidence: 99%
“…34 AA16e35 and AA34e53 in k-casein were also Time-related differences in the binding of IgE and IgG4 to epitopes of b-lactoglobulin, a-lactalbumin, and caseins between patients with early recovery or persistent cow's milk allergy have been investigated. 101,102 Furthermore, IgE and IgG4 epitope binding was also analyzed to predict the outcome of oral immunotherapy in cow's milk allergy using peptide arrays. 103 The results of this study showed that monitoring the binding of IgE and IgG4 to epitope peptides of caseins has predictive value for the development of tolerance to cow's milk or the outcome of oral immunotherapy.…”
Section: B-casein (Bos D 11)mentioning
confidence: 99%
“…Neuere Untersuchungen gibt es bereits auf Epitopebene aus derselben Arbeitsgruppe: Mithilfe eines Microarrays, basierend auf Peptiden der Kuhmilcheinzelallergene, konnten Savilahti et al [38] zeigen, dass ein breiteres Spektrum von IgE-Reaktivitäten und eine höhere Konzentration peptidspezifischer IgE vor SOTI mit Kuhmilch einen Prädiktor für Therapienebenwirkungen und das Ausbleiben des Therapieerfolgs darstellten [38].…”
Section: » Die Spezifische Orale Toleranzinduktion Birgt Noch Ein Grounclassified
“…In a trial of milk OIT, the investigators found decreased IgE binding and increased IgG 4 binding to cow milk epitopes among children who achieved desensitization. Those who discontinued OIT due to adverse effects had increased quantity and affinity of epitope-specific IgE antibodies and less overlap between IgE and IgG 4 binding to milk peptides [62] . These results suggest that analysis of IgE and IgG4 binding to allergens and their specific epitopes may assist in predicting outcomes and improving the safety of OIT.…”
Section: Prediction Of a Favorable Response To Oitmentioning
confidence: 99%